Preparation and characterization of core‐shell polystyrene/polyaniline/Pd composites and their catalytic properties for the reduction of 4‐nitrophenol. Issue 19 (9th January 2017) - Sun, Libo; Sun, Xun; Zheng, Yuhua; Lin, Qingquan; Su, Huijuan; Wang, Yunxia; Qi, Caixia
ABSTRACT: Herein, polystyrene/polyaniline/Pd (PS/PANI/Pd) core‐shell composite catalysts were prepared by a facile swelling‐diffusion‐interfacial polymerization method. PS microparticles were firstly prepared by dispersion polymerization and were swollen by aniline monomer without any surface modification. H2 PdCl4 acid was used as palladium precursor. The PdCl 4 2 − was adsorbed on the surface of aniline‐swollen PS microparticles because of the electrostatic attraction between PdCl 4 2 − and anilinium positive ions protonated by H +, which was diffused from the aniline‐swollen PS microparticles. Then HCl solution was added to control the diffusion rate of anilinium positive ions and ammonium persulfate (APS) was used to polymerize the anilinium ions to get PANI shell. Due to the redox activity between PANI and Pd ions, Pd nanoparticles can be in situ formed on the surfaces of PS. Therefore, the core‐shell PS/PANI/Pd composite catalysts were obtained. The morphology and structure of the obtained composites was characterized by TEM, FT‐IR and EDX. Results showed that the products presented excellent catalytic properties for the reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) in the presence of NaBH4 by virtue of the interaction between Pd nanoparticles and conducive PANI shell. The catalytic reaction obeyed the pseudo‐first‐order reaction equations and the reaction rate constants were also calculated in this article. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44812. Abstract :